Universidade popular comunitária : a importância da comunidade na educação de jovens e adultos - Silva, Loedilza Milicia da (2020)
This research arose from my questions as a teacher of Youth and Adult Education (EJA) when I searched for methodologies and practices that met the real needs of students in this modality. These wishes led me to know the Community Popular University (UPC), a differentiated form of adult education in peripheral communities of the Cuiabana capital, between 2002 and 2010. Thus, the writing of this dissertation comes from the following question: how can a curriculum elaborated from the community reality stimulate the daily life in the Education of Youth and Adults? For the development of this research, the general objective is to understand how the differentiated practices of the UPC helped in the consolidation of an identity that was expressed in the collective, affirmative construction and in the repercussion of a community whose pedagogical and cultural success is to have built a living curriculum, in the way of a popular education of reference. This objective was parted in the following specific objectives: to describe and analyze, from the bibliographic and biographical research with artisentis (teachers) and coartisentis (students) of the UPC, relating the impact of the actions experienced by these subjects in their lives; to analyze, after a conversation round and interviews with those involved, the contributions of the UPC to the development of the communities where their campuses existed; demonstrate, through bibliographic studies, that involvement between the school and the community can be a viable alternative to attract and maintain EJA students. It is also important to emphasize that the products created after each student passes through the spaces of causation, helped in their financial, intellectual, professional, and political growth, contributing to the strengthening of a liberating popular education. In this context, this research has a qualitative phenomenological approach merleau-pontyan, also using documentary and biographical research. Therefore, the research methodology was developed based on Lüdke and André, Almeida, Mattos, Silva and Souza and several official documents. As for the theoretical foundation, Freire, Arroyo, Brandão, Boaventura de Souza Santos, Gadotti, and others that deal with popular education: Streck, Carrillo, Gohn and Peruzzo. Regarding the theme on community and geographical space, subsidies were sought in Bauman, Boff, Carrillo, Raffestin, Santos, Siqueira and Tönier. From the analysis of the data obtained, it is concluded that the UPC was able to develop a relevant popular education with great success for those involved.